Agglomeration and Sorting - Determinants of Regional Productivity Differentials. A Theoretical and Empirical Investigation. - Haenle, Philipp (Kovac, 2014)
In der theoretischen Analyse wird ein Modell entwickelt, das die Lokation von Arbeitern mit unterschiedlichem Humankapital untersucht. Hierbei kann sich das Humankapital in zweifacher Weise unterscheiden: Zum einen nach dem Niveau der Bildung, zum anderen nach dem Gebiet, in dem die Bildung erworben wurde. Die theoretische Untersuchung zeigt, dass Arbeiter mit höherem Bildungsniveau sich eher in urbanen Regionen niederlassen als geringer qualifizierte Arbeitnehmer. Denn Arbeiter mit höherer Bildung können besser von Agglomerationsökonomien profitieren als schlechter qualifizierte Arbeitnehmer. Ein weiteres Ergebnis der Untersuchung ist, dass es zu regionalen Spezialisierungen in den Wissens- und Fähigkeitsgebieten der Arbeiter kommen kann, wenn die konkrete Ausgestaltung der Agglomerationsökonomien sich regional unterscheidet. Die theoretischen Erkenntnisse werden empirisch überprüft. Hierzu wird ein Paneldatensatz für 412 deutsche Stadt- und Landkreise über die Jahre 1996 bis 2008 verwendet. Neben Informationen zu formalen Bildungsabschlüssen werden auch Variablen einbezogen, die die regionale Berufsstruktur einer Region beschreiben. Diese Variablen dienen der detaillierten Messung des von der regionalen Wirtschaft eingesetzten Humankapitals.

Productivity differentials of workers between urban and rural regions are usually explained by increasing returns to scale due to agglomeration. These increasing returns to scale are called agglomerations economies. We contribute to the literature as we analyse regional differences in agglomeration and individual location decisions of workers jointly. We use a panel dataset for 412 German Nuts3-regions for the years from 1996 to 2008. Beside detailed formal educational data our dataset comprises information about 33 different fields of profession. The information about the professions serves as detailed proxies for the skills possessed by the workers. In the first empirical chapter we analyse the vertical sorting model. Checking for endogeneity, year- and region specific effects we can confirm the conclusions from our theoretical analysis: Employees profit heterogeneously form density. Agglomeration may thus be a driving force of workers sorting. In the second empirical chapter we investigate horizontal sorting. We first identify regional specialisations in the occupational structure and group regions with similar structures together. Second, we analyse the impacts of agglomeration in the different clusters on labour productivity. The empirical results commit the theoretical implications: We find evidence for horizontal sorting such that workers with skills in different fields locate in different regions. We further find that workers in these specialised regions profit differently from agglomeration. Lastly, we examine inter-regional integration and its dependence on the occupational profiles of the regions.
Keywords: Arbeitsmarkt; Region; Verdichtungsraum; Einflussgröße; Berufsqualifikation; Bildung; Arbeitnehmer; Mobilität; Wirtschaftsentwicklung; Regionalwirtschaft; Regionale Disparität; Sozioökonomie; Längsschnittuntersuchung; Regionaler Arbeitsmarkt; Humankapital; Arbeitsproduktivität